Implementasi Pengelolaan Kualitas Dan Pengendalian Pencemaran Air Di Home Industry Krupuk Desa Kenanga Sindang Indramayu - Nurwahyuni, Nurwahyuni (Jurnal Suara Hukum, 2021)
The impact of modernization in the industrial sector has the potential to produce waste as residual products that can pollute the environment, damage and / or endanger health and the environment. Actualization of these threats is contrary to the ecologically Sustainable Development Principle which requires preservation of functions and controlling environmental pollution and damage. The disposal of waste from the production of krupuk Home Industry in Kenanga Village, Sindang Subdistrict, is channeled into a river which is a source of water for the community, causing river pollution. This research is a normative juridical research, based on normative analysis, legal science approach. Primary data as the main data is obtained from various legal materials related to research, supported also by secondary and tertiary data as additional data. The results showed that the implementation of Indramayu Regency Regional Regulation Number 9 of 2012 concerning Water Quality Management and Water Pollution Control, has not been implemented properly. This is evident from the existence of river pollution which is the source of water in Kenanga Village, Sindang Subdistrict, Indramayu Regency, which can no longer be used for people's daily lives due to the waste of krupuk production. The legal responsibility of cracker producers in the management of production waste as stipulated in Article 28 of Indramayu Regency Regulation Number 9 of 2012 concerning Water Quality Management and Water Pollution Control, which is subject to administrative sanctions in the form of a written warning, is deemed not to have a deterrent effect